Effect of a silvopastoral system with Tithonia diversifolia (Hemsl.) A. Gray on the ruminal microbial community of Siboney de Cuba male cattle - Galindo Blanco, Juana L.; Iraola Jerez, J.; Herrera Villafranca, Magaly (Cuban Journal of Agricultural Science, 2025)
To evaluate the effect of silvopastoral system with Tithonia diversifolia on the ruminal microbial community of Siboney de Cuba genotype cattle in growth-fattening, a total of 24 non-castrated animals were used. Two treatments were established: 1) grazing on improved and natural grasses and 2) grazing in a silvopastoral system of T. diversifolia grasses, associated in 100 % of the area. The animals grazed for 24 hours on 10 hectares (ha) of improved grasses, divided into two systems of 5 ha each. The crude protein in the control treatment was 9.54 %, while in the SPS it was 10.5 % in the grass and 22.7 % in Tithonia. In the rumen of animals that grazed in the SPS with Tithonia, the total number of viable bacteria was higher (p<0.0001), while the proteolytic bacteria were 47.17 x 105 CFU/mL and those of the control treatment, 19.42 x 105 CFU/mL, which represents 2.43 times fewer bacteria. There were no effects on the number of cellulolytic fungi. The silvopastoral system increased the number of cellulolytic bacteria and the protozoa were reduced 3.5 times. Methane production was 37.0472 g/kg of digested OM with grasses and in the SPS with Tithonia 34.788 g/kg of digested OM. It is concluded that the rumen microbial community of Holstein x Zebu non- castrated cattle that grazed in SPS with Tithonia showed a higher number of total viable bacteria, proteolytic bacteria, cellulolytic bacteria, a lower number of protozoa and less CH4 compared to the control that grazed in grass areas.